Location of seedborne fungi associated with discoloured maize seeds - V.K. AGARWAL, MANOJ KUMAR and (Indian Phytopathology, 2002)
The location of seedborne fungi in different parts of discoloured maize seeds was determined by seed component plating and microtomy. Seedborne inoculum of Bipolaris maydis [Cochliobolus heterostrophus] (responsible for black and white streaks), Botryodiplodia theobromae (responsible for black pointed dots), Curvularia lunata [Cochliobolus lunatus] (responsible for dark black streaks) and Fusarium moniliforme [Gibberella fujikuroi] (responsible for white streaks) were detected in all components (tip cap, pericarp, embryo and endosperm) of maize seeds, whereas Curvularia pallescens [Cochliobolus pallescens] and Bipolaris carbonum were detected in the tip cap and pericarp; and tip cap, pericarp and endosperm regions, respectively.